The Effect of Tokopedia’s Online Advertising Value and Features on Consumers’ Use Behavior: A Study Utilizing UTAUT2 - Kenny Masbagusdanta; Arif Imam Suroso; Bagus Sartono (LPPM Universitas Terbuka, 2026)
Purpose – This research examined the conditions as well as effects of Tokopedia's online video advertising value using UTAUT2 as the main framework. It also examined other factors that impact behavioral intention as well as Tokopedia's mobile application usage. Methodology – An online questionnaire was utilized to gather data from 191 respondents. The target respondents were YouTube users who watched Tokopedia’s online video ads as well as operated the Tokopedia mobile application. The collected data were subsequently examined using Structural Equation Modeling with SmartPLS. Findings – The results showed that entertainment as well as informativeness positively affected Tokopedia’s advertising value. Furthermore, habit, facilitating conditions, hedonic motivation, as well as effort expectancy positively affected behavioral intention to utilize the Tokopedia mobile application. Behavioral intention and habit also significantly affected use behavior. Originality – This study integrated the UTAUT with the advertising value model to investigate the influence of Tokopedia’s online video ads on the application usage.